Aplikasi Gel Kitosan Berat Molekul Tinggi dan Rendah terhadap Ketebalan Epitel Mukosa pada Proses Penyembuhan Luka Pencabutan Gigi - Fransiska Amelia Hartono; Puguh Bayu Prabowo; Syamsulina Revianti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Acceleration of wound healing after tooth extraction is the most important. One of the tissue repair in wound healing is the reepithelialization. Chitosan is a biomaterial that can be used to accelerate reepithelialization in the wound healing process. Purpose: The aim of this study was to prove the differences between application of chitosan gel high molecular weight and low molecular weight to accelerate the reepithelialization in socket healing after tooth extraction. Material and Methods: The experiment was held the post test only control group design used 24 male wistar rats divided into 3 group. K1 group was control groupwhich was extracted without any treatment, K2 group was extracted and applicated by low molecular weight of chitosan gel, K3 group was extracted and applicated by high molecular weight of chitosan gel. After treatments on the 7 day, all groups of rats were euthanized and the epithelial mucosal thickness was measured under light microscope magnificant 100x. All of the data were analyzed by one way ANOVA and LSD test. Result: This study showed the epithelial thickness of the K2 and K3 groups was significantly higher than K1 group, but there were not significantly different between K2 and K3 group. Conclusion: The effectivity of high molecular and low molecular weight chitosan gel to accelerate reepithelialization in socket healing are similar.